SUFI INFLUENCE AND THE PHILOSOPHY OFLOVE IN THE THOUGHT OF ZAHIRIDDINMUHAMMAD BABUR - Khamdamov Bekhzod Khabibovich (Western European Studies, 2025)
This article explores the profound impact of Sufi thought on the philosophy of love in the writings of Zahiriddin Muhammad Babur (1483–1530), founder of the Mughal Empire and a celebrated poet-thinker. Drawing upon Babur’s lyrical poetry and Baburnama, the study analyzes how love (‘ishq) functions not only as a personal emotion but as a metaphysical principle, ethical discipline, and spiritual path. Influenced by classical Sufi thinkers such as Rumi and Hafiz, Babur’s concept of love bridges the earthly and the divine, the aesthetic and the ethical. His descriptions of nature, beauty, and longing reflect a mystical worldview in which the soul’s journey toward God is mirrored in emotional experience. Love becomes a mode of knowing, a force of purification, and a foundation for moral leadership. The article argues that Babur’s Sufi-inspired philosophy of love constitutes a core element of his intellectual and spiritual legacy
Keywords: Zahiriddin Muhammad Babur; Sufism; philosophy of love